APPLICATIONS foster parents foster GROUP ON THE REMOTE PELITA HEART (KAPH) MENGGUNAKKAN Dreamweaver 8.0, PHP AND MYSQL - Dita Ningtyas; Irfan .,SKom., MMSI Irfan .,SKom., MMSI (Jurnal Sistem Informasi, 2008)
Website on the Internet is an effective means to convey information a product or acompany with fast, accurate, and can accounted for authenticity.KAPH (Pelita Heart Care Group) as a group of volunteers in the field communitydevelopment. Formed to help children scavengers in the area Valley struck III to obtain adecent education at a formal level. For implementation used server side scriptingprogramming language PHP (Personal Home Page) for information on the site can beaccessed through the Internet and utilize MySQL software so that the contents of the sitemore interesting and dynamic.This website is expected that the openness of financial problems accurate and faster withtheir preparation so that it can knit cooperation both in the future.